The Imported Goods System in Iranian Customs Code and Article 07 of GATT Agreements - Sadeghi, Mohammad; Arvanaghi, Mehrdad Jamal (Revue jurisprudence; Vol 11 No 01 (2019): مجلة الاجتهاد القضائي, 2019)
Recently, some new articles have been added to Iranian Customs Code - 2011 and its implementing regulation regarding methods of determining value of imported goods. New articles are markedly different from the traditional practices of the former Customs Code. Former Customs Code has been amendment by government in the light of implementation of the GATT Article 7 but Customs interference as legal issue is still open to question. This research would examine role of such interference on sustainability of market and its equilibrium practices. Furthermore, the research would be concluded by identifying advantage and disadvantage of customs and other organizations interference through application new methods for determining value of imported goods and a legal proposal to reform.